Puszcza Borecka jako cenna ostoja ptaków leśnych - Rąkowski, Grzegorz (Leśne Prace Badawcze, 2016)
This paper presents an overview of bird research carried out in the Borki Primeval Forest during the last 30 years. The Borki Primeval Forest can be considered as one of the most important forest bird sites in Poland. Its avifauna comprises 139 breeding species, including 11 rare and endangered species listed in the Polish Red Data Book of Animals as well as 30 species listed in Annex I of the EU Birds Directive. Despite its relatively small area, the Borki Primeval Forest holds at least 1% of Polish breeding population of as many as 12 bird species. For seven out of these species it is one of the most important breeding sites in the country. The avifauna of the Borki Primeval Forest consists mostly of typical forest birds including 24 indicator species which are associated with natural forests. The richness of bird species in the Borki Primeval Forest and the abundance of several valuable groups of breeding species are the result of a high landscape and habitat diversity as well as a relatively small anthropopression combined with a high degree of naturalness of forest stands.